2020
DOI: 10.1016/j.fgb.2020.103383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular crosstalk between the endophyte Paraconiothyrium variabile and the phytopathogen Fusarium oxysporum – Modulation of lipoxygenase activity and beauvericin production during the interaction

Abstract: Plants comprise many asymptomatic fungal endophytes with potential roles of plant protection against abiotic and biotic stresses. Endophytes communicate with their host plant, with other endophytes and with invading pathogens but their language remains largely unknown. This work aims at understanding the chemical communication and physiological interactions between the fungal endophyte Paraconiothyrium variabile and the phytopathogen Fusarium oxysporum. Oxylipins, common means of communication, such as 13-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…A previous study showed that anaerobic fungal genomes encode a wide array of biosynthetic enzymes of natural products including secondary metabolitessmall, bioactive molecules known to mediate a variety of interactions between microorganisms [54][55][56][57]. The majority of these genes were not significantly differentially expressed between co-culture and monoculture conditions on the various substrates in this study.…”
Section: Fungal Co-culture With a Methanogen May Enhance Pfl Function And Production Of Bottleneck Enzymes In Sugar Pathwaysmentioning
confidence: 57%
“…A previous study showed that anaerobic fungal genomes encode a wide array of biosynthetic enzymes of natural products including secondary metabolitessmall, bioactive molecules known to mediate a variety of interactions between microorganisms [54][55][56][57]. The majority of these genes were not significantly differentially expressed between co-culture and monoculture conditions on the various substrates in this study.…”
Section: Fungal Co-culture With a Methanogen May Enhance Pfl Function And Production Of Bottleneck Enzymes In Sugar Pathwaysmentioning
confidence: 57%
“…Secondary metabolites, although not strictly necessary for the growth or survival of an organism under all growth conditions ( 22 ), are often secreted during antagonistic relationships between microorganisms ( 23 25 ). Previous work mining the high-quality genomes of anaerobic fungi revealed that anaerobic fungi are capable of synthesizing secondary metabolites ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that anaerobic gut fungi synthesize natural products to compete with other microbes for survival in their native environment. Natural products are known to serve a variety of functions to their producers in other environments, including oxidative stress tolerance ( 16 ), fungal development ( 17 ), and antibiosis ( 18 ). Similarly, the natural products of anaerobic gut fungi may serve directly (by antibiosis) or indirectly (by conferring environmental stress tolerance) to allow the fungi to persist despite being outnumbered by other members of the rumen community.…”
mentioning
confidence: 99%